Tabularity: Poetic Structure in Shelley, Agamben, Badiou, and Husserl. Issue 2 (August 2017) - Watkin, William
Abstract : The recent history of the intense relationship between philosophy and poetry has concentrated on the poiesis of poetic language. Poiesis is the truth-revealing nature of poetic materiality and linguistic singularity. The 'truth' it reveals is that truth itself, as expressed by philosophy, is under erasure in a manner that cannot be expressed philosophically, and so must instead be performed poetically. At the same time, however, what has been neglected is the manner by which material poiesis, for example lineation, is located within a wider poetic structure. If a poem disrupts what Badiou calls dianoia, at the local or linear level, it constructs meanings at the 'global' level in the form of its structure. So that while poems may be gifted with truth-revealing poiesis, they are also dominated by truth-developing structures. So far a philosophical interaction with these structures is lacking. This article will consider the philosophical nature of a poem's structure as a means of generating local and global poetic meanings through a development of what will be called poetry's tabularity. Using Shelley's 'Ode to the West Wind', it will consider the work of Agamben, Badiou, and Husserl in relation to how meaning is generated across the poetic, two-dimensional, or tabular field.